The effect of creatine on the developing rat foetus - Badenhorst, Frans Hendrik (My University, 2004)
Creatine is one of the most frequently or generally used ergogenic substances. It is used by professional and amateur athletes and the “man on the street”. Creatine is involved in energy production and protein synthesis in muscle. Although studies have been carried out on the effect of creatine on adults, no study has yet determined whether creatine would have an influence on the developing rat foetus if taken by a female during pregnancy. The aim of this study was thus to determine whether creatine had an effect on the developing foetus
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Medicine Johannesburg,
Keywords: Creatine; Fetus; Rats